Assessment of articular disc with mri in patients with disc displacement of temporo-mandibular joint - MRI the game changer - Suvarna R Gavhane; Avinash Kshar; Raghavendra Byakodi; Arati Paranjpe; Sunil Awale; Manishkumar D Shete (Wolters Kluwer Medknow Publications, 2023)
Background: The temporomandibular joint (TMJ) is considered a complex joint. Temporomandibular disorders (TMDs) are a common cause of musculoskeletal pain. At least one TMD symptom is seen in 33% of the population and 3.6% to 7.0% of the population shows significant severity warranting treatment. Magnetic resonance imaging (MRI) is better for the evaluation of disc and adjacent soft-tissue structures compared to cone beam computed tomography. MRI allows articular disc assessment in open and closed mouth positions. MRI has 95% accuracy in the assessment of disc disorders and 93% accuracy for osseous changes. Materials and Methods: A cross-sectional study was performed with a sample size of 21 patients as per inclusion and exclusion criteria. MRI findings were noted and compared with clinical findings. Results: As per our study, the most common age group is between 20 and 35 years. Of 42 TMJ, 41 joints show disc displacement changes and one TMJ was normal. Disc displacement with reduction is less than disc displacement without reduction. Left TMJ is more affected as disc displacement without reduction, as compared to the right side. Two TMJ were with posterior DD. Four TMJ shows anteromedial and 4 TMJ shows anterolateral DD. Six joints have a subluxation. Conclusion: In our study, we found that MRI in TMDs is more reliable and accurate for the diagnosis of DD.